Paeonol Attenuates Quorum-Sensing Regulated Virulence and Biofilm Formation in Pseudomonas aeruginosa - Yang, Dan; Hao, Suqi; Zhao, Ling; Shi, Fei; Ye, Gang; Zou, Yuanfeng; Song, Xu; Li, Lixia; Yin, Zhongqiong; He, Xiaoli; Feng, Shiling; Chen, Helin; et al. (Frontiers in Microbiology, 2021)
With the prevalence of multidrug-resistant bacteria and clinical -acquired pathogenic infections, the development of quorum-sensing (QS) interfering agents is one of the most potential strategies to combat bacterial infections and antibiotic resistance. Chinese herbal medicines constitute a valuable bank of resources for the identification of QS inhibitors. Accordingly, in this research, some compounds were tested for QS inhibition using indicator strains. Paeonol is a phenolic compound, which can effectively reduce the production of violacein without affecting its growth in C. violaceum ATCC 12472, indicating its excellent anti-QS activity. This study assessed the anti-biofilm activity of paeonol against Gram-negative pathogens and investigated the effect of paeonol on QS-regulated virulence factors in Pseudomonas aeruginosa. A Caenorhabditis elegans infection model was used to explore the anti-infection ability of paeonol in vivo. Paeonol exhibited an effective anti-biofilm activity against Gram-negative bacteria. The ability of paeonol to interfere with the AHL-mediated quorum sensing systems of P. aeruginosa was determined, found that it could attenuate biofilm formation, and synthesis of pyocyanin, protease, elastase, motility, and AHL signaling molecule in a concentration- and time-dependent manner. Moreover, paeonol could significantly downregulate the transcription level of the QS-related genes of P. aeruginosa including lasI/R, rhlI/R, pqs/mvfR, as well as mediated its virulence factors, lasA, lasB, rhlA, rhlC, phzA, phzM, phzH, and phzS. In vivo studies revealed that paeonol could reduce the pathogenicity of P. aeruginosa and enhance the survival rate of C. elegans, showing a moderate protective effect on C. elegans. Collectively, these findings suggest that paeonol attenuates bacterial virulence and infection of P. aeruginosa and that further research elucidating the anti-QS mechanism of this compound in vivo is warranted.